PERANCANGAN METODE ARCHITECTURE SMART CITY - Ichwani, Arief (JIK: Jurnal Ilmu Komputer, 2018)
Smart city is a concept of managing city resources effectively and efficiently. The purpose of this study is to produce a new method in designing the smart city data architecture which can be implemented and adopted easily. This study is carried out by the analysis of the city by using Soft Systems Methodology (SSM) and Business System Planning (BSP) which can generate Collaboration System Methodology, a new method for designing the Smart city Data architecture.Keywords: Smart City, SSM, BSP, Collaboration System Methodology.